2022
DOI: 10.1101/2022.03.08.483459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multimodal chromatin profiling using nanobody-based single-cell CUT&Tag

Abstract: Probing epigenomic marks such as histone modifications at a single cell level in thousands of cells has been recently enabled by technologies such as scCUT&Tag. Here we developed a multimodal and optimized iteration of scCUT&Tag called nano-CT (for nano-CUT&Tag) that allows simultaneous probing of three epigenomic modalities at single-cell resolution, using nanobody-Tn5 fusion proteins. nano-CT is compatible with starting materials as low as 25 000 cells and has significantly higher resolution than… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…However, alternative reagent schemes that allow simultaneous antibody incubations and tagmentation while maintaining target fidelity may increase the number of targets that can be profiled in a single experiment. Innovations in protein engineering, such as fusing Tn5 directly to an antibody, may aid such efforts 58,59 . In the future, we anticipate that development of chromatin-integrated multimodal 30,60 and spatial 61 single-cell technologies will benefit substantially from multifactorial profiling by pairing its potential benefits in cross-factor developmental analysis with strong existing cell type identification and tissue-contextual molecular signatures.…”
Section: Discussionmentioning
confidence: 99%
“…However, alternative reagent schemes that allow simultaneous antibody incubations and tagmentation while maintaining target fidelity may increase the number of targets that can be profiled in a single experiment. Innovations in protein engineering, such as fusing Tn5 directly to an antibody, may aid such efforts 58,59 . In the future, we anticipate that development of chromatin-integrated multimodal 30,60 and spatial 61 single-cell technologies will benefit substantially from multifactorial profiling by pairing its potential benefits in cross-factor developmental analysis with strong existing cell type identification and tissue-contextual molecular signatures.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we found that the performances of all methods largely benefited from being run on high coverage cells, and that these performances did not stagnate on the available data, suggesting that future improvements of protocols - increasing coverage, such as in [34] - will surely provide additional information and granularity to refine embeddings.…”
Section: Discussionmentioning
confidence: 93%
“…Multifactorial CUT&Tag has been used to profile up to three different epitopes in single cells, with no fixed upper limit. An important recent advance in in situ chromatin profiling has been the use of nanobodies, single‐chain camelid antibodies, fused to MNase 78 or Tn5, 29,30 where higher efficiencies are achieved by leaving out the Protein A “middleman.” Multifactorial single‐cell CUT&Tag results from the addition of two differentially barcoded nanobody‐Tn5 fusions, one specific for rabbit primary antibodies and the other for mouse. In one study, multifactorial nanobody CUT&Tag was preceded by ATAC‐seq with pA‐Tn5 loaded with different barcoded adapters 30 .…”
Section: Single‐cell Chromatin Profilingmentioning
confidence: 99%
“…ChEC-seq Micrococcal Nuclease (MNase) fused to protein of interest (POI) [9] CUT&RUN MNase fused to Protein A bound to antibody to POI [10,11] pA-DamID Dam DNA methyltransferase fused to Protein A [12] CUT&RUN. ChIP Supernatant from CUT&RUN used as input for ChIP [13] CUT&Tag Tn5 fused to Protein A bound to antibody to POI [14][15][16][17] CUTAC Low-salt tagmentation of promoter epitope for accessibility [18,19] Tip-seq CUT&Tag with in vitro transcription-based amplification [20] HiCuT Antibody-targeted HiC with a CUT&Tag readout [21] CUT&Flow CUT&Tag with FACS for cell cycle-dependent profiling [22] Paired-Tag Joint single-cell CUT&Tag and RNA-seq [23,24] Epi-DamID Joint single-cell DamID and RNAseq [25] CUT&Tag.pro Joint single-cell CUT&Tag and cell-surface antigen profiling [26] CUT&Tag2for1 Joint single-cell deconvolution CUT&Tag [19] Multi-CUT&Tag Multifactorial single-cell CUT&Tag [27,28] Nano-CUT&Tag Multifactorial single-chain antibodies fused to Tn5 [29,30] Spatial-CUT&Tag Tissue single-cell CUT&Tag [31] RT&Tag Proximity labeling of chromatinassociated RNAs [32] with an antibody to an epitope-tagged chromatin POI.…”
Section: Defining Feature Refsmentioning
confidence: 99%
See 1 more Smart Citation